Low‐Viscosity Limonene Dimethacrylate as a Bio‐Based Alternative to Bisphenol A‐Based Acrylic Monomers for Photocurable Thermosets and 3D Printing. Issue 8 (30th June 2020) - Schimpf, Vitalij; Asmacher, Anne; Fuchs, Andre; Stoll, Klaus; Bruchmann, Bernd; Mülhaupt, Rolf
Abstract: Bisphenol A glycidyl methacrylate (BisGMA) is well established as photocurable resin in dental restoratives and 3D printing. At present there are raising concerns regarding the estrogen‐mimicking bisphenol A (BPA) contamination of health care and consumer products. It is an important challenge to substitute BPA‐based resins for bio‐based cycloaliphatic monomers while lowering resin viscosity without sacrificing high stiffness and glass temperature. Particularly high viscosity is critical for 3D printing by photopolymerization. Unlike BPA the cyclic monoterpene limonene, extracted from citrus fruit peels, is safe in human uses. Herein it is reported on limonene‐based dimethacrylate (LDMA) tailored for 3D printing application and derived from limonene oxide (LO) and methacrylic acid (MA). Residual MA is converted into glycerol dimethacrylate (GDMA) serving as an in situ reactive diluent. The influences of temperature, catalysts, MA/LO stoichiometry, and the addition of glycidyl methacrylate (GMA) and magnesium oxide on the LDMA‐based resin performance are elucidated. As compared to BisGMA (560 Pa s) LDMA‐based resins exhibit significantly lower viscosity (5–117 Pa s) governed by the MA/LDMA molar ratio and the GMA addition. At 30 wt% LDMA content photocured resin yields thermosets having high Young's Modulus (3.4–3.7 GPa), tensile strength (88–98 MPa), and glass transition temperature (119–135 °C), surpassing the performance of the corresponding BisGMA‐based resins. Abstract : The conversion of limonene oxide with methacrylic acid yields hydroxy‐functional limonene dimethacrylate (LDMA) exhibiting low resin viscosity. LDMA outperforms bisphenol A‐based resins and holds promise regarding applications in 3D printing and photocure of bio‐based thermosets.